Using linear positioning transducers to improve snatch performance in weightlifters - Kozub, F. M.; Walker, A. (Strength and Conditioning Journal, 2025)
This article examines how to use linear position transducers to support training for weightlifters performing the snatch. These commercially available devices provide valuable velocity data from the first pull, transition, and through the second pull, which all occur before the athlete rotating under the bar for the catch. Athletes benefit from this discussion given the need to maximize training repetitions before fatigue. Velocity data are useful in applying autoregulation principles before workouts and during training sessions. An individualized approach helps weightlifting coaches identify errors and avoid loss of velocity during key points in the lift. This includes determining each lifter's threshold velocities for successful lifts. Deviations from a successful lift/velocity profile (following a missed lift) help identify where errors occur or if fatigue is a factor. This is important to support technique in lifters who are not represented in the published studies. Examining velocity data in conjunction with video analysis provides information needed to prescribe auxiliary exercises or loads for pulling exercises to ensure that velocity loss is minimized. Velocity feedback helps lifters select loads for successful repetitions that produce a desired force profile and result in improved snatches contributing to higher totals during competition.